Flow-Field Characteristics of High-Temperature Annular Buoyant Jets and Their Development Laws Influenced by Ventilation System - Yi Wang; Yanqiu Huang; Jiaping Liu; Hai Wang; Qiuhan Liu (The Scientific World Journal)
The flow-field characteristics of high-temperature annular buoyant jets as well as the development laws influenced by ventilation system were studied using numerical methods to eliminate the pollutants effectively in this paper. The development laws of high-temperature annular buoyant jets were analyzed and compared with previous studies, including radial velocity distribution, axial velocity and temperature decay, reattachment position, cross-section diameter, volumetric flow rate, and velocity field characteristics with different pressures at the exhaust hood inlet. The results showed that when the ratio of outer diameter to inner diameter of the annulus was smaller than 5/2, the flow-field characteristics had significant difference compared to circular buoyant jets with the same outer diameter. For similar diameter ratios, reattachment in this paper occurred further downstream in contrast to previous study. Besides, the development laws of volumetric flow rate and cross-section diameter were given with different initial parameters. In addition, through analyzing air distribution characteristics under the coupling effect of high-temperature annular buoyant jets and ventilation system, it could be found that the position where maximum axial velocity occurred was changing gradually when the pressure at the exhaust hood inlet changed from 0 Pa to −5 Pa.